The Mitki and the art of postmodern protest in Russia - Mihailovic, Alexandar (Madison, Wisconsin The University of Wisconsin Press, 2018)
Introduction: Post modern, or The Mitki's chronicle of Russian leadership -- Glimmer twins of the Leningrad underground: the creation of Dmitri Shagin in Vladimir Shinkarev's Mitki -- "Who is this heroic man?": David Bowie and the Mitki's queering of masculinity -- Fire water: alcoholism and rehabilitation in the St. Petersburg of the Mitki -- Mosaic authorship: a coproduction of Olga and Aleksandr Florensky -- Satire, sex, and chance: the creative diary of Viktor Tikhomirov -- Conclusion: Icarus rising, or The Mitki against twenty-first-century Russia -- Appendix: Vladimir Shinkarev, "In praise of the bioler room
Includes bibliographical references (pages 239-247) and index
Keywords: Gruppa "Mitʹki; Gruppa "Mitʹki"; Art movements -- Russia (Federation) -- Saint Petersburg -- History -- 20th century; Avant-garde (Aesthetics) -- Russia (Federation) -- Saint Petersburg -- History -- 20th century; Art -- Political aspects -- Russia (Federation); Art ; Political aspects; Avant-garde (Aesthetics); Art movements; ART ; History ; General; History; Russia (Federation) ; Saint Petersburg; Russia (Federation)